Predictors of quality of life among the elderly in Ibadan Metropolis, Oyo State (2018)
This study examined the extent to which depression, social support, socioeconomic status, and religiosity predicts quality of life among the elderly in Ibadan metropolis. Descriptive survey research design of correlation type was used in the study. Six major communities were randomly selected within Ibadan metropolis and three hundred elderly men and women with mean age of 70.7years comprising of 187(62.3%) females and 113 (37.7%) males selected using purposive sampling technique participated in the study. Instruments used for data collection were,; Zung Self-rating Depression Scale (.73), Perceived Social Support Scale (.81), Spirituality Scale (.79), World Health Organization Quality Life Questionnaire (WHOQOL BRIEF .89), Socio-economic Status Scale (.73). Data analyzed using Pearson Product Moment Correlation (PPMC) and Multiple regression analysis at 0.05 level of significant. Social support made the most significant contribution to the prediction of quality of life (β = .408, p<.05), socio-economic status (β=.277, <p.05), religiosity (β=.232, p<0.05) while depression yielded (β= .013 p<0.05). Precisely the predictors contributed 51.8 %( adjusted R2 = 0.518) to the variance of the criterion variable. Based on the findings, it was recommended that social support network of the elderly should be strengthened through the family system .to enhance their quality of life